A bibliometric analysis of the landscape of measuring technology maturity in the enterprise internet of things - Solis Pino, Andrés Felipe; Ruiz, Pablo H.; Mon, Alicia; Collazos, Cesar Alberto (International Journal of Electrical and Computer Engineering (IJECE), 2024)
The internet of things (IoT) is an emerging technology that has taken great relevance in the current socioeconomic context, especially in the business environment, due to its ability to generate competitive advantages. Its adoption presents challenges, such as understanding the value proposition, staff training, and ensuring connectivity and compatibility. In addition, it is crucial to establish the technological maturity of the IoT in enterprises to determine their current state and take steps to address these challenges. In this study, a bibliometric analysis of 431 articles from different scientific databases was performed using Bibliometrix and VOSviewer tools to determine the current state of the domain. The results indicate that the field is booming, with an annual growth rate of 22.58%. Its conceptual structure is composed of the IoT implemented in different contexts, in conjunction with the influence of sister technologies such as big data and blockchain, suggesting limited specificity in establishing the maturity of the enterprise IoT. Countries such as China and Brazil were found to be at the forefront in the area. A promising aspect is establishing standardized ways to measure technological maturity and provide guidelines for improving internet of things adoption.